Demogeographic processes in the Western regions of Ukraine on the eve of the reform of territorial authorities - Zablotovska, Natalia; Kondurian, Vladyslav (Human Geography Journal, 2024)
Demogeographic processes are an indicator of societal development that responds most actively to any changes. Geographers interpret demogeographic terminology in different ways, but they unanimously agree on the importance of comprehensive research into the demogeographic development of a territory both in time and space. By the end of the second decade of the 21st century, several directions in demographic research had formed among social geographers: purely theoretical and methodological approaches, studies of the territorial peculiarities of demogeographic processes at the state level, and attempts at typology on a local level. With the implementation of the administrative-territorial reform, the problem of comprehensive spatial-temporal research arose at the level of both old and new administrative districts for a significant area. We conducted a typology of demogeographic processes within the administrative regions of Western Ukraine at the level of administrative districts based on the administrative-territorial structure before 2020, covering the period from 1990 to 2020. The conducted research showed that stable types of demogeographic processes are mainly found in the foothill, mountainous, and border areas. Specifically, in the foothills and mountains, there is a predominance of the positive type, with the regional centers joining them. However, in border areas, we clearly observe a population decline due to mechanical outflow. Nevertheless, the main type of geodemographic processes in all western regions of Ukraine is consistently negative, with a decrease in population primarily due to natural decline with minor mechanical outflow. Thus, by early 2020, when statistical observations transitioned to a new stage of collection and processing (according to new administrative districts), in the western regions of Ukraine, despite general negative demographic trends, it was possible to identify demographically positive Carpathian, Polissian, and Lviv areas, as well as demographically favorable territories around regional centers.